ChemInform Abstract: A Facile One‐Pot Domino Reaction for the Stereoselective Synthesis of Acryl Derivatives Promoted by Ca(OTf)2. Issue 35 (11th August 2016) - Yaragorla, Srinivasarao; Saini, Pyare Lal; Pareek, Abhishek; Almansour, Abdulrahman I.; Arumugam, Natarajan
Abstract: Facile multicomponent reactions for the synthesis of indolyl and oxindolyl acrylates as well as bisacrylates are presented.